Math bilang - Callanta, Ma. Irene I.; del Castillo, Marion S.; Gaerlan, Ma. Joan.; Molato, Maricris M.; Palomique, Norleen O. (2001)
Several systems for gesture recognition have been developed using different strategies and approaches. This paper describes a system for real time gesture recognition, which can distinguish a small vocabulary of about 14 different, static hand gestures. The fourteen gestures are representatives for actions of Addition, Multiplication, Division, Subtraction and the numbers One to Ten. A voice translation of the mathematical expression and its corresponding answer is also part of this system. Our approach uses two-dimensional images of hand postures. The pattern recognition is employed using the back propagation algorithm. All the computation occurs on a SGI workstation. Experiments with our system achieved recognition accuracy up to 90%. Our system uses input from a monocular color video camera.
Thesis (B.S. Computer Science)--University of the Philippines Diliman.
Keywords: Human-computer interaction; Gesture -- Data processing; Image processing -- Digital techniques -- Mathematical models; Optical pattern recognition -- Mathematical models; Neural networks (Computer science); Hand gesture recognition